2012
DOI: 10.1590/s0366-69132012000200017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airborne particle abrasion protocols on surface topography of Y-TZP ceramic

Abstract: This study aimed to evaluate Y-TZP surface after different airborne particle abrasion protocols. Seventy-six Y-TZP ceramic blocks (5×4×4) mm 3 were sintered and polished. Specimens were randomly divided into 19 groups (n=4) according to control group and 3 factors: a) protocol duration (2 and 4 s); b) particle size (30 µm, alumina coated silica particle; 45 µm, alumina particle; and 145 µm, alumina particle) and; c) pressure (1.5, 2.5 and 4.5 bar). Airborne particle abrasion was performed following a strict pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…Regarding particle size, Queiroz et al noticed a large difference between R a and R z values in particle abraded specimens due to the presence of deep valleys in the surface for tested specimens. When the 145 μ m alumina particles were used, R z achieved the highest value, suggesting that large particles promoted more punctual damage in a surface than small particles, regardless of the pressure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding particle size, Queiroz et al noticed a large difference between R a and R z values in particle abraded specimens due to the presence of deep valleys in the surface for tested specimens. When the 145 μ m alumina particles were used, R z achieved the highest value, suggesting that large particles promoted more punctual damage in a surface than small particles, regardless of the pressure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 12 , 14 19 , 45 ] Previous stand-alone studies using sandblasting or UVP have reported significant increase in surface roughness as compared to untreated surfaces, and the results obtained in this study are in line with these findings. [ 4 12 , 13 15 , 17 20 , 21 46 ] Comparative studies on surface roughness caused by these surface treatments are lacking, and hence further correlations on this aspect of this study results cannot be drawn.…”
Section: Discussionmentioning
confidence: 94%
“…Airborne particle abrasion with alumina particles lesser than 100 µm in size has been identified as a key factor in achieving an optimum surface roughness to enhance biological response of osteoblasts without causing structural damage to zirconia. [ 9 11 , 18 20 21 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…When a size of 110 μm of particles was used in the tribochemical treatment, Ra and Rz achieved the highest values, suggesting that large particles under pressure induced damage on the surface, which is in accordance with published papers. 38,39 In this study, Ra and Rz were measured to give a better picture of the surface topography, to detect shape of irregularities (valleys and peaks). 40 The surface hardness (VHN) of the tested groups ranged from 703 to 1758.…”
Section: Discussionmentioning
confidence: 99%